Heart failure in low risk patients with atrial fibrillation, nationwide registry case-control study based on 227811 patients. (14th October 2021) - Basic, C; Hansson, P; Zverkova-Sandstrom, T; Johansson, B; Fu, M; Mandalenakis, Z
Abstract: Background: Heart failure (HF) is common in patients with atrial fibrillation (AF), and also associated with worse outcome. Consequently, it is commonly included in risk prediction models for AF, used in daily clinical praxis. However, knowledge about the association between solely AF and incidental HF is limited. Aim: This study aims to evaluate the short and long-term risks for onset of HF in patients with AF and low cardiovascular risk profile. Methods: All patients with first recorded hospitalization for AF in the Swedish National Patient Register, were included from the 1St January 1987 to 31st December 2018. Each patient with AF was matched by age, sex and county with two controls from the Swedish Total Population Register. Patients <18 years, or with concomitant hypertension, diabetes mellitus, coronary and periphery artery disease, previous stroke or transitory ischemic attack, cardiomyopathy, pulmonary arterial hypertension, congenital heart disease, valvular heart disease and renal failure prior or at baseline were excluded. Results: In total 227 811 patients and 452 712 controls met the inclusion and exclusion criteria and were included in the study. The incidence rate for incidental HF per 1000 person-year within one year after AF diagnosis was 6.2 (95% CI: 4.5–8.6) among patient 18–34, increased with increasing age and was 142.8 (95% CI: 139.4–146.3) among those >80 years. Within five years the incidence rate decreased in all age categories and was 2.4 (95% CI: 1.8–3.0) among the youngest and 94.0 (95% CI: 92.4–95.6) in the oldest age group. When compared to matched controls from the general population patients with AF had a hazard ratio (HR) and CI 95% to develop HF within one year at 103.9 (46.3–233.1), 34.9 (26.5–45.9), 17.5 (15.5–19.8), 10.3 (9.6–11.1) and 6.1 (5.8–6.4) among patients aged 18–34, 35–49, 50–59, 60–69, 70–79 and >80 years, respectively. Conclusion: Despite low cardiovascular risk profile AF still carries high risk for developing incidental HF in particular during the first observation year with increasing tendency along with increasing age. Younger patients with AF and without other cardiovascular comorbidities had more than 100 times higher relative risk to develop HF within one year when compared to matched controls. Funding Acknowledgement: Type of funding sources: None.